Entre lugares, entre olhares: as performances da escrita de Pedro Juan Gutiérrez - Gabriela Figueiredo Azevedo (2016)
In this dissertation, regarding the intrinsic relationship between esthetic and politic, as postulated by the philosopher Jacques Rancière, we try to reflect on Havana`s Dirty Trilogy, The King of Havana and Dialogue with my Shadow: about the writers work, from the cuban author Pedro Juan Gutiérrez, as engaged esthetic practice, which causes tensions and makes questions for the sensible universe defined by our police regime of the sensible. Using the performative writings theories, as proposed by Graciela Ravetti, we think about the strategies that the author uses to compose these new regimes of visibility. We also discuss how the author, through a socio-spatial repositioning, changed his writer style. In this sense, we reflect on these first two works, Havanas Dirty Trilogy and The King of Havana that gave him birth as a Latin American author as representatives of a first phase of Gutiérrezs writing, in which we recognize a cathartic writing performance, designing voices and images that serves like testimonies of individuals who, by our sensitive regime, were not invited to exist. Dialogue with my Shadow in turn, marks a new phase of the author's writing, in which he, away from the universes in crisis that led him to write his first works, produces an autobiographical and meta literary writing performance, which plays with limits of genres, of the fictional universe and the author himself.